2018
DOI: 10.1371/journal.pone.0203027
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in postmenopausal plasmatic lipidome

Abstract: BackgroundMenopause consists of a physiological process in women between 40 and 50 years of age, and it has substantial consequences for health, ranging from disturbances in lipid and glycidic metabolism to psychological stress and sleep alterations, thereby increasing women’s risk of cardiovascular diseases. Here, we attempted to identify potential lipid alterations not identified by the classic methods.Methods and resultsWe analyzed the serum lipid profile in 40 women in pre- and post-menopause using a lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It was found that the serum concentrations of oxidative damage markers (e.g., TBARS, AOPP, PCG) were higher, and the serum indices of antioxidant abilities parameters (e.g., GSH) were lower in postmenopausal women than in premenopausal women [ 33 , 34 , 35 ]. In addition, the glucose and lipid metabolism disorders are observed in postmenopausal women [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the serum concentrations of oxidative damage markers (e.g., TBARS, AOPP, PCG) were higher, and the serum indices of antioxidant abilities parameters (e.g., GSH) were lower in postmenopausal women than in premenopausal women [ 33 , 34 , 35 ]. In addition, the glucose and lipid metabolism disorders are observed in postmenopausal women [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the prevalence of overweight, represented by overweight and obesity, among the elderly female population raises great concern in developed and developing countries. Since overweight and obesity are risk factors for adverse health events[2], such as disturbances in lipid and glucidic metabolism, psychological stress and sleep alterations, there is an increased risk of cardiovascular diseases[3], musculoskeletal disease, acute myocardial infarction[4], cancer[5] and worse quality of life[6] among patients who are overweight and obese in comparison to those who are satisfied with their body weight[7].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the comparison of lipid profiles and fasting glucose among the groups, it was shown that only TC and LDL-c significantly varied between pre- and postmenopausal women. In a recent study carried out at outpatient facilities of the same hospital of the current study [17], postmenopausal women also presented with increased levels of VLDL-c and TC. Similarly to our findings, these authors observed no differences in HDL, fasting glucose levels and hs-CRP.…”
Section: Discussionmentioning
confidence: 77%
“…Follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol, progesterone, total cholesterol (TC), high-density lipoprotein (HDL-c), triglycerides (TG) and high sensitivity C-reactive protein (hs-CRP) were measured using a COBAS 6000 automated analyzer (Roche Diagnostics, Mannheim–Germany), following the manufacture instructions. The concentrations of low-density (LDL-c) and very low-density lipoproteins (VLDL-c) were calculated through the Friedwald formula (VLDL = TG/ 5; LDL-c = TC–HDL-c–VLDL-c) for TG values of up to 4.5 mmol/L [1617]. Circulating leptin and iterleukin(IL)-6 levels were estimated using enzyme-linked immunosorbent assay (Quantikine ® ELISA kits, R&D Systems, Inc., Minneapolis, MN, USA), according to the manufacture instructions.…”
Section: Methodsmentioning
confidence: 99%